Receiver scheme of rake equalization for 60GHz pulse communication system - Xian CHEN; Xuehua LI (Dianxin kexue)
Dispersion of the signal energy and the inter symbol interference（ISI）is caused by the multipath fading in 60GHz pulse communication environment.To solve this problem,the severity of the ISI in the system was analyzed,and the method to eliminate interference was studied.Based on the 60GHz wireless channel model established by IEEE 802.15.3c,the simulation platform of 60GHz pulse communication system was built.Theoretical analysis and numerical simulation of ISI in the system were carried out,and a receiver scheme of combining Rake receiver and equalizer was designed.Results show that,the two taps MRC-Rake receiver module combined with MMSE linear equalization module can not only improve the signal energy by multipath diversity,but also eliminate ISI.The performance of the system was improved without increasing the complexity.The scheme provides a reference for the design of 60GHz pulse communication system in the future.